Regulations of the Effects of Adoption in the Romanian Civil Code - CIOCOIU, Mariana (Journal of Advanced Research in Law and Economics; Vol 7 No 7 (2016): JARLE Volume 7, Issue 7(21), Winter 2016, 2017)
Effects of adoption impact upon parental rights and obligations, surname, home and domicile of the adopted, as well as his/her citizenship, both on what national and international adoption are concerned. Given the distinction between national and international adoption, similarly, the effects of adoption can be analysed on two levels, as, in the case of international adoption, there occurs the specific issue of recognising the effects of the Romanian court decisions abroad. The research presents the effects of adoption according to the new Romanian Civil Code.